2000
DOI: 10.1074/jbc.m007480200
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bonds of GM2 Synthase Homodimers

Abstract: GM2 synthase is a homodimer in which the subunits are joined by lumenal domain disulfide bond(s). To define the disulfide bond pattern of this enzyme, we analyzed a soluble form by chemical fragmentation, enzymatic digestion, and mass spectrometry and a fulllength form by site-directed mutagenesis. Ganglioside synthesis is regulated during differentiation, development, and malignant transformation (1-3) and occurs in the Golgi apparatus by the stepwise addition of monosaccharides to glycolipid acceptors by mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 54 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…Chen et al (53), on the other hand, demonstrated that one isoform of ST6Gal I forms disulfide-linked homodimers, which stay in the Golgi. The formation of disulfide-linked homodimers has been also reported for ␣1,2-fucosyltransferase, GM2 synthase, and ␤1,3-glucuronyltransferase (51,54,55). For GM2 synthase, homodimers are formed in anti-parallel orientation, and such a dimeric formation is apparently essential for its activity (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (53), on the other hand, demonstrated that one isoform of ST6Gal I forms disulfide-linked homodimers, which stay in the Golgi. The formation of disulfide-linked homodimers has been also reported for ␣1,2-fucosyltransferase, GM2 synthase, and ␤1,3-glucuronyltransferase (51,54,55). For GM2 synthase, homodimers are formed in anti-parallel orientation, and such a dimeric formation is apparently essential for its activity (54).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of disulfide-linked homodimers has been also reported for ␣1,2-fucosyltransferase, GM2 synthase, and ␤1,3-glucuronyltransferase (51,54,55). For GM2 synthase, homodimers are formed in anti-parallel orientation, and such a dimeric formation is apparently essential for its activity (54). In contrast, ␤1,3-glucuronyltransferase that adds the first glucuronic acid in proteoglycan synthesis (55) forms a functional homodimer in parallel orientation through a cysteine in the stem region.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Young and colleagues (21,22) showed that disulfide-bonded dimers of the GM 2 synthase form in the ER, that the disulfide bonds are formed between the catalytic domains of two monomers, and that the active form of the enzyme is a disulfide-bonded dimer. More recent work from these researchers showed that these intercatalytic domain disulfide bonds are formed in an anti-parallel manner between Cys-80 and Cys-82 with Cys-412 and Cys-529 (27).…”
Section: Discussionmentioning
confidence: 99%
“…This distinctive arrangement is similar to that occurring in ␣(1,3/1,4) fucosyltransferase III (51) and polysialyltransferase ST8Sia IV (52), where site-directed mutagenesis demonstrated that such steric conformation may be associated with acceptor substrate specificity (53,54) and catalytic efficiency (52), respectively. Similarly, the catalytic activity of GM2 synthase depends on the formation of disulfide-bonded homodimers, whose antiparallel orientation also brings the N and C termini in close proximity, most likely to establish a catalytic domain (55).…”
Section: Discussionmentioning
confidence: 99%